Measuring offenders’ belief in the possibility of desistance - O’Sullivan, Kevin (International journal of offender therapy and comparative criminology, 2018)
This article describes the use of a questionnaire to measure offenders’ belief in the likelihood of their making a successful re-entry into society after having committed crime, a “belief in redeemability” (BIR) as described by Maruna and King. The 37 items for the scale were taken from statements by offenders about their prospects of making good. This set of items was tested with a pilot group of offenders recruited from clients on parole or on supervised bonds at community corrections offices in metropolitan Sydney, Australia, and their responses were coded to yield a score we called the “BIR” score. We found that scores displayed variance skewed toward an optimistic view, and we then used the items in a card sort task with a panel of graduate psychologists to explore whether the panel could identify underlying components of the broader BIR. There was a measure of agreement on three underlying components and these were further tested using five raters. We called the components that emerged the following: Belonging, Agency, and Optimism; Cronbach’s alphas for these indicated acceptable internal consistency. The results are discussed in terms of their congruence with findings in the literature and their use in correctional practice.